Prioritäre Stoffe in kommunalen Kläranlagen. Ein deutschlandweit harmonisiertes Monitoring. - Toshovski, Snezhina; Kaiser, Maria; Sacher, Frank; Thoma, Astrid; Kümmel, Veronika; Lambert, Benedikt (My University, 2020)
Über das kommunale Abwassersystem (Kläranlagen, Regen- und Mischwassereinleitungen) gelangt eine Vielzahl von Stoffen in die Gewässer. In dem von den Ländern finanzierten, koordinierten Projekt wurden deutschlandweit 49 Kläranlagen und ausgewählte Regenwasserbehandlungsanlagen auf prioritäre Stoffe untersucht. Ziel war die Schaffung einer validen Datenbasis zur Beurteilung der Relevanz der urbanen Eintragspfade für Schadstoffe in die Gewässer. Die 77 untersuchten Stoffe waren unterschiedlich häufig im Ablauf der Kläranlagen und Regenwasserbehandlungsanlagen zu finden. Für 30 Stoffe konnten mittlere Ablaufkonzentrationen zur Quantifizierung der Stoffeinträge in die Gewässer abgeleitet werden.

The aim of this project, which was methodologically harmonized and coordinated between the federal states, was to improve the existing database for the quantification of emissions of priority substances from municipal wastewater treatment plants. For this purpose, the effluents of 49 municipal wastewater treatment plants representatively distributed across Germany were sampled. In five of the 49 plants, additional investigations of inflow and sludge pathways were conducted. They form the basis for the assessment of the retention performance of conventional waste water treatment plants for priotity pollutants. In addition, two storm water outlets and six combined sewer overflow tanks were sampled. In all samples 54 individual substances like heavy metals, industrial chemicals, perfluorinated compounds, polycyclic aromatic hydrocarbons, pesticides and standard waste water parameters were examined. Sensitive, partly newly developed analytical methods were used. A number of substances could not be quantified in any effluent, storm water or combined overflow sample. Some occured only in a few samples. However, for 20 substances which measured above the LOQ in > 50 % of the effluent samples, median, mean concentrations and emission factors could be derived. For these substances, a quantification of the mean emissions in Germany is possible. For a large number of other substances a solid data basis for additional tasks and questions is available.
Keywords: Kläranlage; Kommunalwirtschaft; Entwässerungssystem; Abwasserbelastung; Gewässerverunreinigung; Stoffeintrag; Datenerhebung; Repräsentativerhebung; Monitoring